Perceptions of Country Corruption: Antecedents and Outcomes - Davis, James H. (Journal of business ethics, 2003)
Globalization has increased the need for managers (and future managers) to predict the potential for country corruption. This study examines the relationship between Hofstede's cultural dimensions and how country corruption is perceived. Power distance, individualism and masculinity were found to explain a significant portion of the variance in perceived corruption. A significant portion of country's risk, trade flow with U.S.A., foreign investment, and per capita income was explained by perceived corruption.